Demographics and Characterization of 10, 282 Randall Plaque-Related Kidney Stones. Issue 10 (March 2015) - Letavernier, Emmanuel; Vandermeersch, Sophie; Traxer, Olivier; Tligui, Mohamed; Baud, Laurent; Ronco, Pierre; Haymann, Jean-Philippe; Daudon, Michel; Malindretos., Pavlos
<x xml:space="preserve">Abstract</x> Abstract Renal stone incidence has progressively increased in industrialized countries, but the implication of Randall plaque in this epidemic remains unknown. Our objectives were to determine whether the prevalence of Randall plaque-related stones increased during the past decades after having analyzed 30, 149 intact stones containing mainly calcium oxalate since 1989 (cross-sectional study), and to identify determinants associated with Randall plaque-related stones in patients (case–control study). The proportion of Randall plaque-related stones was assessed over 3 time periods: 1989–1991, 1999–2001, and 2009–2011. Moreover, we analyzed clinical and biochemical parameters of 105 patients affected by calcium oxalate stones, with or without plaque. Of 30, 149 calcium oxalate stones, 10, 282 harbored Randall plaque residues (34.1%). The prevalence of Randall plaque-related stones increased dramatically during the past years. In young women, 17% of calcium oxalate stones were associated with Randall plaque during the 1989–1991 period, but the proportion rose to 59% 20 years later (P < 0.001). Patients with plaques experienced their first stone-related event earlier in life as compared with those without plaque (median age 26 vs 34 years, P = 0.02), had increased ionized serum calcium levels (P = 0.04), and increased serum osteocalcin (P = 0.001) but similar 25-hydroxyvitamin D levels. The logistic regression analysis showed that age (odds ratio [OR] 0.96, confidence interval [CI] 0.926–0.994, P = 0.02), weight (OR 0.97, CI 0.934–0.997, P = 0.03), and osteocalcin serum levels (OR 1.12, CI 1.020–1.234, P = 0.02) were independently associated with Randall plaque. The prevalence of the FokI f vitamin D receptor polymorphism was higher in patients with plaque (P = 0.047). In conclusion, these findings point to an epidemic of Randall plaque-associated renal stones in young patients, and suggest a possible implication of altered vitamin D response.